Insomnia as a Contributor to Hypertension and Somatic Distress: A Case Report - Nihazzatuzzain; Algristian, Hafid; Cahyono, Budi (Psychosocia : Journal of Applied Psychology and Social Psychology, 2025)
Insomnia is increasingly recognized as a systemic disorder involving persistent hyperarousal with broad psychiatric and cardiovascular consequences. This case report describes a 49-year-old woman who developed functional dyspepsia after taking an analgesic, which led to chronic insomnia and, subsequently, essential hypertension (blood pressure reaching 173/93 mmHg) accompanied by generalized somatic distress. Her sleep pattern became non-restorative, with reduced sleep drive and dependence on hypnotics. Psychiatric evaluation revealed Nonorganic Insomnia, a Moderate Depressive Episode, and Somatization Disorder, with an Insomnia Severity Index score of 16. Her clinical course illustrates a psychophysiological cascade. Gastrointestinal distress disrupted sleep architecture, sustained sympathetic nervous system activation, and dysregulated the hypothalamic–pituitary–adrenal axis, thereby contributing to hypertension and somatic amplification. This case highlights the need to view insomnia as a systemic condition rather than an isolated symptom. Early recognition and non-pharmacological interventions—particularly Cognitive Behavioral Therapy for Insomnia (CBT-I)—may prevent long-term cardiovascular and psychiatric complications.